SOSIALISASI PENTINGNYA MANAJEMEN KEUANGAN UNTUK PELAKU UMKM JEMAAT GKP KLASIS JAKARTA DALAM MEMAJUKAN USAHANYA - Ramot Simanjuntak; Nenny Anggraini; Desideria Regina; Juaniva Sidharta (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
The role of Micro, Small and Medium Enterprises (MSMEs) in the Indonesian economy is very important and is the most important pillar in increasing Indonesia's economic growth. In general, especially in the financial aspect, only a few MSMEs have experienced developments in their financial performance. One of the factors that causes this to happen is due to the low awareness of MSME actors on the importance of financial management. Financial records are very important for any business, but MSME actors often ignore this, including members of the Jakarta Klasis Christian Pasundan Church (GKP). The activity and discipline of recording all expenses and income to control finances in business is very necessary. Based on this, it is deemed necessary to provide socialization regarding the importance of Financial Management for MSMEs and is expected to be able to help members of the Jakarta Christian Pasundan Church (GKP) Classes in managing their business finances in a correct, disciplined and orderly manner. The implementation of this community service activity aims to provide socialization on the importance of financial management for MSMEs in the form of a hybrid webinar using the Zoom application (online) .Overall, the socialization activities on the importance of financial management for MSMEs actors can be said to have been successful; seen from the target number of participants, the achievement of socialization goals and the achievement of the material targets that have been planned. The enthusiasm of the participants, support from UKI and the Jakarta Class GKP Assembly were the supports for the implementation of this PkM activity. The benefits that participants get from this activity include understanding financial records for MSMEs in advancing their business. Keywords: financial management, MSMEs